Influence of tedizolid on the cytokine response to the endotoxin challenge in healthy volunteers: a cross-over trial. (15th February 2022) - Jorda, Anselm; Wulkersdorfer, Beatrix; Schörgenhofer, Christian; Matzneller, Peter; Al Jalali, Valentin; Bauer, Martin; Wölf-Duchek, Michael; Lackner, Edith; Dorn, Christoph; Jilma, Bernd; Zeitlinger, Markus
Abstract: Background: Preclinical data suggested anti-inflammatory properties of tedizolid. Objectives: To investigate the influence of tedizolid on the cytokine response to the human endotoxin challenge and the effect of endotoxaemia on the pharmacokinetics and protein binding of tedizolid. Methods: In this cross-over trial, 14 male healthy volunteers underwent two treatment periods: (A) 200 mg of tedizolid phosphate once daily for 6 days (3 days orally and 3 days intravenously), followed by an intravenous bolus of 2 ng/kg body weight of LPS on the last treatment day; and (B) intravenous bolus of LPS (2 ng/kg body weight) without concomitant tedizolid treatment. Participants underwent first period A or B, separated by at least 6 weeks. Plasma was sampled to assess cytokines and the pharmacokinetics of tedizolid. Results: Following the endotoxin challenge, the peak plasma concentration (median [IQR]; 280 [155–502] versus 287 [132–541] pg/mL; P = 0.875) and AUC0–24 (979 [676–1319] versus 1000 [647–1632] pg·h/mL; P = 0.638) of interleukin-6 remained unchanged with and without concomitant tedizolid treatment. The peak concentration and AUC0–24 of TNF-α remained also unchanged with and without tedizolid (47 [31–61] versus 54 [27–69] pg/mL; P = 0.73 and 197 [163–268] versus 234 [146–280] pg·h/mL; P = 0.875, respectively). The total maximum concentration (mean ± SD; 2.94 ± 0.69 versus 2.96 ± 0.62 mg/L), total AUC0–24 (22.3 ± 3.8 versus 21.1 ± 3.6 mg·h/L) and protein binding (21.4% ± 1.7% versus 21.6% ± 1.9%) of tedizolid were similar with and without the endotoxin challenge. Conclusions: Tedizolid did not attenuate the LPS-induced cytokine response in healthy volunteers. Furthermore, endotoxaemia did not influence the plasma pharmacokinetics of tedizolid.